Glycemic load, fiber, magnesium, zinc, physical activity, stress factor and fasting blood glucose level - Ramadhani Tiara Putri; Yulia Wahyuni; Idrus Jus'at (Darussalam Nutrition Journal, 2021)
Background: Diabetes mellitus is a group of metabolic diseases and some of the trigger factors are food intake, physical activity and stress factors. Objective: To know the relationship between glycemic load, intake of fiber, magnesium, zinc, stress levels, physical activity, and fasting blood glucose levels of female Patients with Type 2 Diabetes Mellitus in Cibinong Hospital. Research methods: This research is a quantitative study with a cross sectional study design. The population of this study were all female patients with type 2 diabetes mellitus who attended exercise as many as 30 subjects. Measurement of food intake data used the 3 x 24 recall method. Physical activity data used a 3 x 24 hour recall questionnaire while stress data used the Diabetes Distress Scale (DDS). The data analysis of this research used Pearson correlation, independent sample t test. Research result: The mean age of respondents was 59 years, glycemic load was 127.4 units, fiber intake was 17.31 grams, magnesium 380.5 mg, zinc 6.84 mg. A total of 9 people with moderate stress levels, physical activity PAL value of 1.81 and fasting blood glucose levels 138.23 mg / dL. There is a relationship between glycemic load (p = 0.003), fiber intake (p = 0.03), magnesium (p = 0.001), physical activity (p = 0.043) and fasting blood glucose levels. There was no relationship between zinc intake and fasting blood glucose levels (p = 0.178). There was no difference in fasting blood glucose levels based on the subject's stress level (p = 0.161).Conclusion: Glycemic load, fiber intake, magnesium and physical activity are all factors that affect fasting blood glucose levels.